Plasticity in the cell division processes of obligate intracellular bacteria - Harpring, McKenna; Cox, John V. (Frontiers in Cellular and Infection Microbiology, 2023)
Most bacteria divide through a highly conserved process called binary fission, in which there is symmetric growth of daughter cells and the synthesis of peptidoglycan at the mid-cell to enable cytokinesis. During this process, the parental cell replicates its chromosomal DNA and segregates replicated chromosomes into the daughter cells. The mechanisms that regulate binary fission have been extensively studied in several model organisms, including Eschericia coli, Bacillus subtilis, and Caulobacter crescentus. These analyses have revealed that a multi-protein complex called the divisome forms at the mid-cell to enable peptidoglycan synthesis and septation during division. In addition, rod-shaped bacteria form a multi-protein complex called the elongasome that drives sidewall peptidoglycan synthesis necessary for the maintenance of rod shape and the lengthening of the cell prior to division. In adapting to their intracellular niche, the obligate intracellular bacteria discussed here have eliminated one to several of the divisome gene products essential for binary fission in E. coli. In addition, genes that encode components of the elongasome, which were mostly lost as rod-shaped bacteria evolved into coccoid organisms, have been retained during the reductive evolutionary process that some coccoid obligate intracellular bacteria have undergone. Although the precise molecular mechanisms that regulate the division of obligate intracellular bacteria remain undefined, the studies summarized here indicate that obligate intracellular bacteria exhibit remarkable plasticity in their cell division processes.